PENGARUH SERTIFIKAT HALAL TERHADAP TINGKAT PENJUALAN AYAM SEGAR PT. ADIL MART PONTIANAK - Ana Yuliana (Jurnal Ekonomi Integra, 2013)
In this papers, we investigates relation between Halal Certified and sale quantity. This study use chi square analysis to provide result about the set of problem. Based on study analysis, that any relation between Halal certified and sale quantity. From chi square analysis found X2 statistic (63.663,35) ≤ X2 table (19,68), that mean any relation between Halal certified and sale quantity.